San Francisco Municipal Reports for the Fiscal Year 1874-5, Ending June 30, 1875, at 886 (1875) - (:unkn) unknown (My University, 1887)
General Orders, Order No. 1,226-Prohibiting the Carrying of Concealed Deadly Weapons, § 1. Approved July 9, 1875: Prohibited the concealed carry of any pistol, dirk, or other dangerous or deadly weapon.
Keywords: CARRY - CONCEALED